THE PLAYING AND PLAYFUL: PERSPECTIVES ON IMPORTANT USE OF THE MATERIALS IN AQUATIC DIDACTICS SWIMMING LESSONS OF INFANT (Fiep Bulletin - online, 2013)
The playful relationship in teaching in liquid medium reaches a human dimension that goes beyond mere entertainment or as a reward for completion of tasks during the lessons of swimming, it enables reveal emotions and sensations, as well as aspects related to affection. In the classes for swimming, a new look at the pedagogical practice based on learning mediated by social and cultural elements has been a concern in the choice of content and how they will be taught. The extension program of "Good Neighborhood" aims to promote leisure and social development of children and adolescents from poor communities. The methodology used in the research was quantitative, using a questionnaire as a tool for evaluation. Subjects were 15 participants, between eight and fifteen years, of both sexes, residents of the neighborhoods surrounding the UFJF. The results showed that 53.33% like most of the activities with games, educational exercises 26.67%, 13.33% favor enhance the swim and the remaining 6.67%, has other tastes. Regarding the teaching materials used, 46.67% identified the "bottle" as a favorite, the pasta 33.33%, 13.33% have a preference for board and only 6.67% like the Halter. About the activities, 46.67% showed interest in taking objects on the bottom of the pool, 20% in the rotation of board, 20% jump in the pool and 13.3%, with activities in two. Given the nature of their work, their target audience, the favorite activities of participants and the teaching material used
Keywords: Swimming; Materials; Playful